Penerapan Metode Studi Kasus dan Pemecahan Masalah pada Pembelajaran Adaptasi Budaya Kerja (pada Peserta Pelatihan Bahasa Jepang Kelas Kecil di LPK Sekai Jepang Tasikmalaya) - Haura Mutiara; Muhammad Irsan; Rindu Bilqis Khoerunnisa; Vanya Ramania Yasmin; Ghefira Nafisa; Ratna Kurniasih; Lesi Oktiwanti (Universitas Pahlawan Tuanku Tambusai, 2026)
The objective of this community service activity is to foster an understanding of the Japanese work culture through the application of case study and problem-solving methods at LPK Sekai Japan Tasikmalaya. This activity used lectures, case studies, and problem-solving to present the aforementioned activities in a single session. The material covered work ethics, professional communication, and teamwork, as well as Japanese work culture values such as kaizen, ganbatte, and bushido. A pre-test was administered, and data on student performance after instruction was collected through the following instruments: a post-test, observation, and focused group discussions. The results of the activity showed an increase in participants’ knowledge from the pre-test (average score of 60.25) to the post-test (average score of 85.25). Furthermore, participants became more active in their participation, adopted a critical mindset, and were better able to frame workplace issues. Therefore, the application of case study and problem-solving methods is effective in enhancing the readiness of individuals joining as participants in Japanese work culture, and can serve as an alternative learning model in vocational training institutions.